Atrial fibrillation and the use of oral bisphosphonates - Michael Pazianas; Cyrus Cooper; Yiting Wang; et al (Dove Medical Press, 2011)
Michael Pazianas1, Cyrus Cooper1,2, Yiting Wang3, Jeff L Lange4, R Graham G Russell1,51The Botnar Research Centre, Oxford University, Oxford, UK; 2MRC Epidemiology Resource Centre, University of Southampton, Southampton, UK; 3Warner Chilcott Pharmaceuticals, USA; 4Procter & Gamble Company, Cincinnati, OH, USA; 5The Mellanby Centre for Bone Research, Sheffield University, Sheffield, UKBackground: Epidemiological studies investigating a possible association between bisphosphonates and atrial fibrillation (AF) have reported conflicting findings. The objective of our study was to determine whether exposure to oral nitrogen-containing bisphosphonates alendronate and risedronate are associated with increased incidence of atrial fibrillation.Methods: In a retrospective cohort study we analyzed data from three large independent databases, two from the United States (MarketScan® and Ingenix®) and one from the United Kingdom (THIN). 144,548 women, age 50–89, bisphosphonate users during 2002–2005 were compared to 668,891 sex- and age-matched controls (1:4). Our primary outcome measure was new incident atrial fibrillation for up to three years; Cox models adjusted for disease and drug history were used to estimated relative risks.Results: We identified a total of 8,001, 1,984, and 817 AF cases in oral bisphosphonate users and nonusers during 744,340 (MarketScan), 243,898 (Ingenix), and 148,779 (THIN) person-years of follow-up, respectively. Compared to nonusers, overall adjusted relative risk (adjRR) (95% confidence interval [CI]) for AF in oral bisphosphonates users was 0.92 (0.85–0.99; MarketScan), 1.00 (0.87–1.16; Ingenix), and 0.97 (0.79–1.20; THIN); overall adjRR (95% CI) for any cardiac dysrrhythmia for MarketScan was 1.01 (0.98–1.05), Ingenix 1.06 (0.99–1.13), and THIN 0.97 (0.79–1.20).Conclusions: In all three databases from the two countries, the risk of AF or cardiac dysrrhythmia was not increased in postmenopausal women treated for up to three years with oral alendronate or risedronate.Keywords: atrial fibrillation, chemically induced osteoporosis, drug therapy, alendronate or risedronate, bisphosphonates, adverse effects